The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1103/physrevlett.97.013001
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond Pulse Trains Generated Using Two Color Laser Fields

Abstract: We investigate the spectral and temporal structure of high harmonic emission from argon exposed to an infrared laser field and its second harmonic. For a wide range of generating conditions, trains of attosecond pulses with only one pulse per infrared cycle are generated. The synchronization necessary for producing such trains ensures that they have a stable pulse-to-pulse carrier envelope phase, unlike trains generated from one color fields, which have two pulses per cycle and a pi phase shift between consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
168
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(180 citation statements)
references
References 23 publications
3
168
0
4
Order By: Relevance
“…Early experiments confirmed that energy, momentum, and parity are preserved when high harmonics are generated in two-color fields [10]. This introduced the potential to control the high-harmonic process [11][12][13], leading to the generation of attosecond pulse trains with individual pulses separated by the laser period [14] and new approaches to isolating a single attosecond pulse [15][16][17] and generating tunable extreme ultraviolet (XUV) radiation [18]. Recently, it has been shown that weak-field control of high harmonic generation allows attosecond pulses to be measured as they are being produced in the medium [19].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Early experiments confirmed that energy, momentum, and parity are preserved when high harmonics are generated in two-color fields [10]. This introduced the potential to control the high-harmonic process [11][12][13], leading to the generation of attosecond pulse trains with individual pulses separated by the laser period [14] and new approaches to isolating a single attosecond pulse [15][16][17] and generating tunable extreme ultraviolet (XUV) radiation [18]. Recently, it has been shown that weak-field control of high harmonic generation allows attosecond pulses to be measured as they are being produced in the medium [19].…”
mentioning
confidence: 81%
“…Our work builds on a long history of experiments on using multiple color fields to produce high harmonics [10][11][12][13][14][15][16][17][18]. Early experiments confirmed that energy, momentum, and parity are preserved when high harmonics are generated in two-color fields [10].…”
mentioning
confidence: 99%
“…Smaller delays τ lead to overlap between the ac and dc components, which are separated by p 0 τ , thus disturbing the retrieval algorithm. Attosecond pulses separated by one IR laser cycle have been demonstrated in high-order harmonic generation (HHG) experiments with two colors (ω,2ω) [24]. Furthermore, the delay of two attosecond pulses can be controlled by means of a segmented mirror [25].…”
Section: Implementation Of Qspidermentioning
confidence: 99%
“…In particular, it has been experimentally demonstrated that single and multiple attosecond laser pulses can be produced by means of the process of high-order harmonic generation (HHG) in rare gases [5,6]. As the length of the incident pulse decreases, the HHG peaks in the cutoff regime are replaced by one or a few pronounced supercontinuum patterns as individual adjacent peaks begin to merge with one another [7,8].…”
Section: Introductionmentioning
confidence: 99%